(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Purpose – The purpose of this research evaluates the profitability of cement industry and compares the profitability of cement companies.Design methodologyapproach – This research study check and compare the profitability of Indian cement industry. We framed the exploratory and descriptive research design to answer the research questions. This study draws a sample of three cement companies as basis on market capitalization. These companies are UltraTech cement Ltd., Shree cement Ltd. and Ambuja cement Ltd. This research study has cover five years data from 2013-14 to 2017-18.Findings – Through analysis of data and results it is found that sampled cement companies perform best on selected profitability parameter. This research compares the profitability performance on different parameter. All sampled cement companies perform the same performance on profitability parameter during the study period. There is no significant difference between profitability of sampled cement companies.Originalityvalue – This research has compared the profitability of cement companies on four parameter of profitability. Through analysis of related literature, we found there have few countable researches which compared the profitability performance of cement companies through statistical tools.